Segmentation Strategy and Company Positioning in Business Development to Increase Competitiveness (Case Study of PT Bangun Desa Logistindo) - Nugraha, Bharata; Pradana, Madi; Simarmata, Juliater (Green Publisher, 2025)
The global logistics industry in Asia has witnessed significant growth, driven by globalization, technological advancements, and the e-commerce boom. Indonesia, with its strategic location and inter-island transportation complexities, offers unique challenges and opportunities. This study explores the business strategies of PT Bangun Desa Logistindo (BDL), a leading domestic logistics provider, using SWOT, IFAS, and EFAS analyses to assess its position in the market. Key strengths identified include BDL’s strategic location, modern facilities, and advanced technologies. However, high operational costs and reliance on infrastructure quality emerge as notable weaknesses. External opportunities, such as the rapid growth of e-commerce and government initiatives like the National Logistics Ecosystem (NLE) program, present avenues for expansion. Conversely, challenges like intense competition, regulatory barriers, and stagnant cargo volume growth persist. The study emphasizes the need for BDL to capitalize on its strengths and external opportunities while mitigating vulnerabilities. Proposed strategies include infrastructure optimization, operational digitization, and strategic partnerships to enhance efficiency and competitiveness. These measures aim to drive sustainable growth, strengthen market positioning, and solidify BDL’s role as a key player in Indonesia’s logistics sector. By aligning internal capabilities with external opportunities, BDL is well-positioned to adapt to industry dynamics and contribute to Indonesia's evolving logistics ecosystem.